Pemanfaatan Limbah Kulit Durian dan Pupuk Organik Cair Urine Kelinci terhadap Pertumbuhan dan Hasil Tanaman Buncis Tegak (Phaseolus vulgaris L) - Sundari (Indoensia), Lilis; sugiyarto (Indoensia), sugiyarto; oktasari (Indoensia), wike (JURNAL VIGOR, 2023)
The aims of the research was to determine the effect dose of durio peel compost and concentration of rabbit urine liquid organic fertilizer on the growth and yield of upright bean plants (Phaseolus vulgaris L). The dose of fertilization is a dose of fertilizer given in units of weight per land area, while the concentration is the amount of solution needed in liters. The research was conducted from July to October 2022 in Tirip Hamlet, Kembaran Village, Candimulyo District, Magelang Regency at an altitude of 437 m asl. The research used a factorial experiment (4x4) which was arranged in a Completely Randomized Block Design (CRBD) with three replications as blocks. The first factor of the dose of durio peel compost is 0, 150, 300, and 450 g. The second factor was the POC concentration of rabbit urine 0, 15, 30, and 45 ml. The results showed that different doses of durio peel compost provide the number of pods per plant, the weight of fresh pods per plant and the protein content. The higher concentration of rabbit urine liquid organic fertilizer increases the weight of fresh pods per plant and the protein content. The dose of durio peel compost fertilizer 300 g and without liquid organic fertilizer rabbit urine provides the highest protein content.